2016
DOI: 10.1021/acsami.6b06624
|View full text |Cite
|
Sign up to set email alerts
|

In situSynthesis of Fluorescent Gold Nanoclusters by Nontumorigenic Microglial Cells

Abstract: To date, the directed in situ synthesis of fluorescent gold nanoclusters (AuNCs) has only been demonstrated in cancerous cells, with the theorized synthesis mechanism prohibiting AuNC formation in nontumorigenic cell lines. This limitation hinders potential biostabilized AuNC-based technology in healthy cells involving both chemical and mechanical analysis, such as the direct sensing of protein function and the elucidation of local mechanical environments. Thus, new synthesis strategies are required to expand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…For intracellular gold nanoparticle formation, all of the constituents (sans chloroauric acid) are innately present in cellular systems. This intracellular gold nanoparticle formation has been demonstrated previously in mammalian cells, however, only through bulk diffusive treatments, lasting more than 24 h, and typically those are in solutions which contain no cell nutrients (such as DPBS) [35][36][37][38][39][40][41][42][43][44][45][46][47] . These treatment scenarios are non-ideal for minimizing the impact on cellular health.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…For intracellular gold nanoparticle formation, all of the constituents (sans chloroauric acid) are innately present in cellular systems. This intracellular gold nanoparticle formation has been demonstrated previously in mammalian cells, however, only through bulk diffusive treatments, lasting more than 24 h, and typically those are in solutions which contain no cell nutrients (such as DPBS) [35][36][37][38][39][40][41][42][43][44][45][46][47] . These treatment scenarios are non-ideal for minimizing the impact on cellular health.…”
Section: Resultssupporting
confidence: 57%
“…Further to this, if cellular machinery are used to generate gold nanoparticles, the resulting plasmon-optical properties could act as a reporter of the affecting cell phenotype. This capability to generate gold nanoparticles via cellular biomolecules has already been demonstrated previously in mammalian cells [36][37][38][39][40][41][42][43][44][45][46][47] . The precise mechanism for this cellular bioreduction of gold nanoparticles is not fully understood, however, these treatments have been known to negatively impact cell health through cellular responses via shock and stress-related proteins 42 , decrease in viability 43,44 , and even cell fixation 44 .…”
supporting
confidence: 63%
See 1 more Smart Citation
“… 20 22 As such, any nonreduced ions are then free to diffuse out of the cell without any cellular interference, essentially being viewed as a “friend” via the presence of endogenous proteins. 4 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…However, in a subsequent study, we demonstrated the formation of fluorescent AuNCs in nontumorigenic mouse microglia in a non-ROS-dependent mechanism. 4 Microglia are a major component of the central nervous system’s immune system, offering first response to exogenous drugs as well as providing immune regulations of other glial cells, namely, astrocytes and oligodendrocytes. 24 Therefore, understanding the interaction, uptake, and response of glial cells to nanoscale materials, such as the fluorescent metal nanoclusters, is critical in developing nano-biotechnologies for future brain studies.…”
Section: Introductionmentioning
confidence: 99%